Effect of Firm Size, Gearing Ratio, and Gender Diversity on Extent of Risk Disclosure - Thea Herawati Rahardjo, Nurainun Bangun, Tri Handayani Amalia (International Journal of Advanced Science and Technology, 2020)
The purpose of this research is to investigate empirical evidence between firm size, gearing ratio, and gender diversity’s impact on extent of risk disclosure in banking companies published on Indonesian Stock Exchange for the period 2016-2018, with a total of 36 sample banking companies that have been previously selected by purposive sampling method. This research uses secondary data taken from the website www.idx.co.id and is processed by panel data regression analysis using EViews 10.0 application. The results reveals that firm size has positive significant effect towards extent of risk disclosure, gearing ratio has negative and significant influence on the extent of risk disclosure, whereas gender diversity insignificantly affect extent of risk disclosure. Keywords: Firm Size, Gearing Ratio, Gender Diversity, Extent of Risk Disclosure.